2015
DOI: 10.1038/jcbfm.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

miR-98 and let-7g* Protect the Blood-Brain Barrier Under Neuroinflammatory Conditions

Abstract: Pathologic conditions in the central nervous system, regardless of the underlying injury mechanism, show a certain level of blood-brain barrier (BBB) impairment. Endothelial dysfunction is the earliest event in the initiation of vascular damage caused by inflammation due to stroke, atherosclerosis, trauma, or brain infections. Recently, microRNAs (miRNAs) have emerged as a class of gene expression regulators. The relationship between neuroinflammation and miRNA expression in brain endothelium remains unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
110
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 39 publications
4
110
0
2
Order By: Relevance
“…Another study has analyzed the therapeutic manipulation of brain endothelial microRNA‐98 and Let‐7g‐3p to prevent BBB dysfunction in neuroinflammation. In this study, the authors identified 2 potential targets, CCL2 and CCL5, by which microRNA‐98 and Let‐7g‐3p may regulate leukocyte adhesion (34). These studies suggest that a brain endothelial microRNA therapeutic strategy aimed at ameliorating BBB dysfunction during neuroinflammation may be beneficiated as a result of microRNAs concomitantly modulating several molecular and cellular processes implicated in neuroinflammation.…”
Section: Therapeutic Potential Of Brain Endothelial Micrornas For Cnsmentioning
confidence: 99%
“…Another study has analyzed the therapeutic manipulation of brain endothelial microRNA‐98 and Let‐7g‐3p to prevent BBB dysfunction in neuroinflammation. In this study, the authors identified 2 potential targets, CCL2 and CCL5, by which microRNA‐98 and Let‐7g‐3p may regulate leukocyte adhesion (34). These studies suggest that a brain endothelial microRNA therapeutic strategy aimed at ameliorating BBB dysfunction during neuroinflammation may be beneficiated as a result of microRNAs concomitantly modulating several molecular and cellular processes implicated in neuroinflammation.…”
Section: Therapeutic Potential Of Brain Endothelial Micrornas For Cnsmentioning
confidence: 99%
“…Let-7g leads to beneficial effects on EC through modulating TGF-β signaling and SIRT-1 signaling (Figure 2) [24], which might contribute to the limitation of local inflammation of plaque and improve vascular thrombosis. In addition, overexpression of let-7g has resulted in the reduction of adhesion and migration of monocytes across endothelium [25].…”
Section: Let-7g and Inflammationmentioning
confidence: 99%
“…MiRs are key regulators of a vast number of biological processes and disorders, including MS14 and those regulating neurovascular function in inflammation15, such as regulation of cell adhesion molecules and leukocyte adhesion to human brain endothelium1216.…”
mentioning
confidence: 99%